GROWTH ANALYSIS OF Glycine max UNDER DIFFERENT IRRIGATION REGIMES AND THREE SPECIES OF ARBUSCULAR MYCORRHIZA - Pirzad, Alireza (Scientia Agraria, 2018)
To evaluate the optimal irrigation system to increase soybean yield, introducing a beneficial species of symbiotic mycorrhizal fungus, and assessment of interaction effect of irrigation×mycorrhiza on the growth of soybean (Glycine max L.), a split plot experiment was conducted based on randomized complete block design with three replications at Urmia University in 2015. Treatments were irrigation systems (drip: D, constant partial root- zone drying irrigation: CPRD, rainy: R, furrow: F and alternate partial root- zone drying irrigation: APRD) and mycorrhizal fungi species (Glomus mosseae, G. intraradices, G. hoi and non-inoculated treatment as control). The binomial regressions for Total Dry Matter (TDM), Leaf Area Index (LAI), Leaf Weight (LW) showed the accumulated increase of biomass production up to 1111 GDDs (96 DAS). The furrow irrigation produced the largest amounts of LAI followed down by LAI in APRD and CPRD irrigation systems, respectively. The same binomial regressions for LAI were observed in mycorrhizal treatment, too. Stem dry weight with the linear increasing for drip irrigation and binomial function for other 4 irrigation systems, show the highest level in drip irrigation. The respective usefulness of stem dry weight was for plants inoculated with G. intraradices, G. mosseae and G. hoi. All irrigation systems and mycorrhizal treatments indicated the linear rises for pod weight along with growing season. We observed a diminishing returns for Relative Growth Rate (RGR) in all irrigation systems and mycorrhizal treatments (G. mosseae, G. intraradices, G. hoi and non-mycorrhizal as control). But, a latest increase in RGR at the end season was occurred. There was a sharp decline for Crop Growth Rate (CGR) at the end of growing season for all irrigation systems. The same cubic function was obtained for all mycorrhizal treatments, with the respective magnitude for non mycorrhizal control than mycorrhizal plants.